Clinical features and course of Angiostrongylus cantonensis eosinophilic meningitis in patients receiving supportive therapy - Sawanyawisuth, Kanlayanee (Food Waterborne Parasitol, 2020)
Acute severe headache is the main presentation of eosinophilic meningitis (EOM) caused by Angiostrongylus cantonensis. Oral corticosteroid treatment is effective in reduction of duration of headache but may be contraindicated in particular patients. This study investigated clinical features and clinical course of eosinophilic meningitis caused by A. cantonensis if left untreated. Additionally, factors associated with duration of headache were evaluated. We conducted a retrospective study between 1997 and 2019 at a university hospital in Thailand. The inclusion criteria were adult patients who were diagnosed with EOM, had a positive serological test for A. cantonensis, received only supportive treatment, and had the complete clinical course documented. Factors associated with duration of headache were executed by multivariate linear regression analysis. A total of 54 patients were used in the final analysis. Of those, 39 patients (79.2%) were male and the mean ± SD age of all patients was 33.7 ± 12.2. The mean ± SD duration of headache was 16.0 ± 12.4 days with the longest duration of 49 days. The only factor associated with duration of headache was gender (p = 0.036). The male gender had a coefficient of −8.4 (95% CI: −16.2, −0.6). The median duration of headache in male and female patients was 11 and 20 days, respectively. In conclusion, A. cantonensis eosinophilic meningitis can cause long lasting headache, and gender may be associated with duration of headache.